A cross-sectional examination of non-Big 4 firms' reliability. Issue 6 (6th July 2015) - Wilson, Reginald
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to examine the impact of service-related independence impairments on perceptions of local and regional non-Big 4 Firms' financial reporting reliability. This study is motivated by recent public policy, which proposes that service-related independence impairments may improve financial reporting reliability. Design/methodology/approach – Commercial lending officers respond to a within-subjects experiment. The variables of interest are client importance, expertise and their related interaction. These variables are regressed on the perceived reporting reliability of local and regional firms. Findings – Client importance is positively and significantly associated with the lenders' selection of non-Big 4 firms, which supports Taylor et al.'s (2003) assertions that service-related independence violations improve financial reporting reliability. However, client importance is negatively associated with regional firms. Practical implications – Client importance is significantly associated with regional firms only, which suggests that cross-sectional differences exist among non-Big 4 firms. The negative association between regional firms and client importance confirms Goldman and Barlev's (1974) concerns that large firms are not exempt from client pressure. Client importance is also significantly (and positively) associated with lenders' selection of the type of non-Big 4 firm to perform the engagement, which supports recent public policy's proposal for joint attest and non-attest services (Exposure Draft for Statement for Accounting and Review Services No. 18). Originality/value – The study overcomes within-subjects design limitations to provide a natural environment to understand lending officers' perceptions of non-Big 4 firms. The results continue to fill the void in the literature which examines cross-sectional differences in non-Big 4 firm quality.